Project-Based Plant Morphology Module as Teaching Material for Students' Concept Mastery - Murniati, Neni; Yennita, Yennita; Cahya, Malinda Dwi; Hasan, Rusdi (Biosfer: Jurnal Pendidikan Biologi, 2025)
The necessity for teaching materials that can effectively facilitate students' skills has become increasingly evident in order to enhance concept mastery. The objective of this study is to develop teaching materials in the form of project-based modules on plant morphology for the purpose of facilitating concept mastery. The Project-Based Plant Morphology Module was developed in accordance with the ADDIE model (Branch, 2009), which comprises five phases: analysis, design, development, implementation, and evaluation. The research instruments utilized for the development process included a validation questionnaire, a student response questionnaire, and a concept mastery test. Validity of the module was obtained through the use of instruments in the form of book validation sheets, which were completed by experts in the fields of media, materials, and education. The module trials were obtained through the implementation instruments for the individual components and the management of the learning implementation. Product trials will be conducted with students enrolled in the Biology Education program during the second semester of the 2022/2023 academic year. The data used to validate the module was obtained from the module's expert validators using a validation sheet. The data obtained from the product trial is analyzed in order to assess the readability of the module. The results indicated that the plant morphology module was classified as "very feasible." The responses of students to the module indicated that it was categorized as "very easy to understand". Consequently, the plant morphology module is deemed a valuable and effective component of plant morphology courses